Plated steel and method for manufacturing plated steel

The plated steel with a Zn-Al-Mg alloy layer and controlled Zn/Al/MgZn23-membered process addresses peeling and corrosion issues, ensuring excellent processability and corrosion resistance in wet environments.

KR103040735B1Active Publication Date: 2026-10-30NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020247032537
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-18
Filing Date
2022-12-16
Publication Date
2026-10-30
Estimated Expiration
2042-12-16

AI Technical Summary

Technical Problem

Plated steels with high Mg concentration in the plating layer experience peeling during processing and reduced corrosion resistance in environments where water accumulates, such as when installed parallel to the ground.

Method used

A plated steel with a Zn-Al-Mg alloy layer on the surface, containing specific chemical compositions and a controlled Zn/Al/MgZn23-membered process, and optionally an Al-Fe alloy layer, with a surface roughness Ra of 0.3 to 2.0 μm, processed to achieve excellent processability and corrosion resistance.

Benefits of technology

The plated steel exhibits improved workability and corrosion resistance even in environments where water tends to accumulate, by uniformly dispersing the Zn/Al/MgZn23-membered process and reducing local corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112024106069541-PCT00009_ABST
    Figure 112024106069541-PCT00009_ABST
Patent Text Reader

Abstract

A plated steel material and a method for manufacturing the same, wherein the plating layer has a predetermined chemical composition, and when the surface of the plating layer is polished to half the thickness of the layer and observed at a magnification of 100x using a scanning electron microscope, a Zn / Al / MgZn23-membered process exists in the reflected electron image of the Zn-Al-Mg alloy layer, and the average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process is 100 to 300 mm / mm2.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to plated steel and a method for manufacturing plated steel. Background Technology

[0002] For example, various types of galvanized steel are used in the field of construction materials. Most of them are Zn-plated steels. Due to the demand for a longer lifespan of construction materials, research on improving the corrosion resistance of Zn-plated steels has been conducted for a long time, and various galvanized steels have been developed. The first high-corrosion-resistant galvanized steel for construction materials was Zn-5% Al galvanized steel (Galvalume galvanized steel), in which Al is added to the Zn-based plating layer to improve corrosion resistance. It is a well-known fact that adding Al to the plating layer improves corrosion resistance; with the addition of 5% Al, Al crystals are formed within the plating layer (specifically the Zn phase), thereby improving corrosion resistance. Zn-55% Al-1.6% Si galvanized steel (Galvalume steel) is also a galvanized steel with improved corrosion resistance for the same basic reasons.

[0003] Here, the appeal of Zn-plated steel lies in its sacrificial protection effect on the base steel. Specifically, at exposed parts of the base steel resulting from cut edges, cracks in the plating layer during processing, or peeling, the surrounding plating layer leaches out before the base steel corrodes, forming a protective film with the leached plating components. This makes it possible to prevent rust from the base steel to some extent.

[0004] Generally, it is desirable for the Al concentration to be low and the Zn concentration to be high, as this effect is more likely to manifest. Accordingly, highly corrosion-resistant plated steels with a relatively low Al concentration of about 5% to 25% have been commercialized in recent years. In particular, plated steels with a low Al concentration and containing about 1% to 3% Mg exhibit superior corrosion resistance compared to plated steels. For this reason, they have become a market trend for plated steels and are currently widely known in the market.

[0005] As a plated steel containing a certain amount of Al and Mg, for example, the plated steel disclosed in Patent Document 1 has also been developed.

[0006] Specifically, Patent Document 1 describes "a plated steel surface having a plating layer composed of Al: 5 to 18 mass%, Mg: 1 to 10 mass%, Si: 0.01 to 2 mass%, the remainder being Zn and unavoidable impurities, wherein an Al phase of 1 mm 2 "Hot-dip Zn-Al-Mg-Si plated steel materials, with more than 200 existing per year, are disclosed."

[0007] In addition, Patent Document 2 describes a plated steel having a plating layer comprising a steel material and a Zn-Al-Mg alloy layer disposed on the surface of the steel material, wherein the plating layer has a chemical composition containing Zn: greater than 65.0%, Al: greater than 5.0% to less than 25.0%, Mg: greater than 3.0% to less than 12.5%, and Sn: 0.1% to 20.0%, wherein, in the back-field electron image of the Zn-Al-Mg alloy layer obtained by observing at a magnification of 100x using a scanning electron microscope after polishing the surface of the Zn-Al-Mg alloy layer to half the layer thickness, Al crystals are present, and the average value of the cumulative periphery length of said Al crystals is 88 to 195 mm / mm 2 "Phosphoric plated steel" is disclosed. Prior art literature

[0008] Japanese Patent Publication No. 2001-355053 WO 2019 / 221193 The problem to be solved

[0009] However, in plated steel with a high concentration of Mg in the plating layer, the plating layer peels off when the plated steel is processed, resulting in reduced workability. In addition, corrosion resistance is reduced in environments where water tends to accumulate, such as when a plated steel sheet is installed and used in a direction parallel to the ground.

[0010] Therefore, the objective of the present disclosure is to provide a plated steel material with excellent processability and excellent corrosion resistance even when used in an environment where water tends to accumulate, and a method for manufacturing the same. means of solving the problem

[0011] The above problem is solved by the following means.

[0012] <1>

[0013] A plated steel having a base steel and a plating layer comprising a Zn-Al-Mg alloy layer disposed on the surface of the base steel, and

[0014] The above plating layer, in mass%,

[0015] Zn: Exceeding 65.00%,

[0016] Al: More than 5.00% and less than 25.00%,

[0017] Mg: greater than 3.00% and less than 12.50%,

[0018] Sn: 0% to 3.00%,

[0019] Bi: 0% to less than 5.00%,

[0020] In: 0% to less than 2.00%,

[0021] Ca: 0% to 3.00%,

[0022] Y: 0% to 0.50%,

[0023] La: 0% to less than 0.50%,

[0024] Ce: 0% to less than 0.50%,

[0025] Si: 0% to less than 2.50%,

[0026] Cr: 0% to less than 0.25%,

[0027] Ti: 0% to less than 0.25%,

[0028] Zr: 0% to less than 0.25%,

[0029] Mo: 0% to less than 0.25%,

[0030] W: 0% to less than 0.25%,

[0031] Ag: 0% to less than 0.25%,

[0032] P: 0% to less than 0.25%,

[0033] Ni: 0% to less than 0.25%,

[0034] Co: 0% to less than 0.25%,

[0035] V: 0% to less than 0.25%,

[0036] Nb: 0% to less than 0.25%,

[0037] Cu: 0% to less than 0.25%,

[0038] Mn: 0% to less than 0.25%,

[0039] Li: 0% to less than 0.25%,

[0040] Na: 0% to less than 0.25%,

[0041] K: 0% to less than 0.25%,

[0042] Fe: 0% to 5.00%,

[0043] Sr: 0% to less than 0.5%,

[0044] Sb: 0% to less than 0.5%,

[0045] Pb: 0% to less than 0.5%,

[0046] B: 0% to less than 0.5%, and

[0047] Having a chemical composition consisting of impurities,

[0048] In the back-field electron image of the Zn-Al-Mg alloy layer obtained by observing the surface of the plating layer after polishing it to half the layer thickness at a magnification of 100x using a scanning electron microscope, a Zn / Al / MgZn23-membered process exists, and the average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process is 100 to 300 mm / mm 2Phosphorized steel.

[0049] <2>

[0050] The plating layer comprises an Al-Fe alloy layer between the base steel and the Zn-Al-Mg alloy layer. <1> Plated steel as described in

[0051] <3>

[0052] The interface roughness Ra between the above-mentioned base steel and the above-mentioned plating layer is 0.3 to 2.0 μm <1> or <2> Plated steel as described in

[0053] <4>

[0054] A substrate steel having a surface roughness Ra of 0.3 to 2.0 μm on the surface to be plated is immersed in a plating bath, and after being lifted from the plating bath,

[0055] Cooling a temperature range of 450 to 395℃ at an average cooling rate of 5 to 20℃ / s,

[0056] Cool the temperature range of 395 to 340℃ at an average cooling rate of 3℃ / s or less, and

[0057] Cooling a temperature range of 340 to 280℃ at an average cooling rate of 10 to 20℃ / s,

[0058] <1> inside <3> A method for manufacturing plated steel as described in any one of the claims. Effects of the invention

[0059] According to the present disclosure, a plated steel material having excellent processability and excellent corrosion resistance even when used in an environment where water tends to accumulate, and a method for manufacturing the same can be provided. Brief explanation of the drawing

[0060] Figure 1 (A) is a reflected electron image of a Zn-Al-Mg alloy layer obtained by observing the surface of the plating layer of the Zn-Al-Mg plated steel of the present disclosure at a magnification of 100x using a scanning electron microscope after polishing it to half the thickness of the layer. Figure 1 (B) is a binary phase of the reflected electron phase of the Zn-Al-Mg alloy layer. Specific details for implementing the invention

[0061] Hereinafter, an example of the present disclosure will be described.

[0062] In addition, in the present disclosure, the "%" indication of the content of each element in the chemical composition means "mass%".

[0063] A numerical range expressed using "inner" refers to a range that includes the values ​​listed before and after "inner" as lower and upper limits.

[0064] In cases where "greater than" or "less than" is attached to the numerical values ​​listed before or after "or," the numerical range refers to a range that does not include these values ​​as lower or upper limits.

[0065] The elemental content of a chemical composition is sometimes expressed in terms of elemental concentration (e.g., Zn concentration, Mg concentration, etc.).

[0066] The plated steel of the present disclosure comprises a base steel and a plating layer comprising a Zn-Al-Mg alloy layer disposed on the surface of the base steel.

[0067] And the plated steel of the present disclosure has a plating layer having a predetermined chemical composition, and in the reflected electron image of a Zn-Al-Mg alloy layer obtained by polishing the surface of the plating layer to half the layer thickness and observing it at a magnification of 100x using a scanning electron microscope, a Zn / Al / MgZn23-membered process exists, and the average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process is 100 to 300 mm / mm 2 am.

[0068] The plated steel of the present disclosure, by means of the above composition, becomes a plated steel with excellent workability and excellent corrosion resistance even when used in an environment where water tends to accumulate. Furthermore, the plated steel of the present disclosure was determined by the following findings.

[0069] In plated steel with a high Mg concentration in the plating layer, a hard intermetallic compound phase is formed within the plating layer. Consequently, when the plated steel is processed, the intermetallic compound phase cracks, making the plating layer prone to peeling.

[0070] Furthermore, when used in environments where water tends to accumulate, the Zn / Al / MgZn23 eutectic in the plating layer corrodes locally, causing corrosion to reach the base metal prematurely.

[0071] Therefore, the Zn / Al / MgZn23-membered process, which causes localized corrosion within the plating layer, is uniformly dispersed. That is, the average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process is kept within a predetermined range.

[0072] By doing so, local corrosion of the Zn / Al / MgZn23-membered process can be reduced. In addition, since the flexible Zn / Al / MgZn23-membered process functions as a buffer during processing, cracking of the surrounding intermetallic compound phase can be reduced.

[0073] From the above findings, it has been discovered that the plated steel of the present disclosure, by means of the above composition, is a plated steel with excellent workability and excellent corrosion resistance even when used in an environment where water tends to accumulate.

[0074] The details of the plated steel of the present disclosure are described below.

[0075] (Substrate steel)

[0076] There are no specific restrictions on the shape of the base steel. In addition to steel plates, examples of formed steel materials include steel pipes, civil engineering materials (ditch fences, corrugated pipes, drainage covers, dust control plates, bolts, metal mesh, guardrails, waterproofing walls, etc.), home appliance components (housings for air conditioner outdoor units, etc.), and automotive parts (suspension components, etc.). Various plastic deformation methods, such as press forming, roll forming, and bending, may be used for forming.

[0077] There are no specific restrictions on the material of the base steel. Various types of base steel may be used, such as general steel, pre-coated steel, Al-killed steel, ultra-low carbon steel, high carbon steel, various types of high-strength steel, and some high-alloy steels (such as steels containing reinforcing elements like Ni and Cr).

[0078] Regarding the base steel material, conditions such as the manufacturing method of the base steel material and the manufacturing method of the base steel sheet (hot rolling method, pickling method, cold rolling method, etc.) are not particularly restricted.

[0079] In addition, as the base steel material, hot-rolled steel sheets, hot-rolled steel strips, cold-rolled steel sheets, and cold-rolled steel strips described in JIS G 3302 (2010) can also be applied.

[0080] The interface roughness Ra between the substrate steel and the plating layer is preferably 0.3 to 2.0 μm.

[0081] By making the surface roughness Ra of the base steel material 0.3㎛ or higher, the average value of the cumulative periphery length of the Zn / Al / MgZn23-element process can be controlled to the above range.

[0082] By making the surface roughness Ra of the base steel material 2.0㎛ or less, unplating is suppressed.

[0083] In addition, the method for measuring the interfacial roughness Ra between the base steel and the plating layer is as described below.

[0084] The base steel may be a pre-plated steel. The pre-plated steel is obtained, for example, by an electrolytic treatment method or a displacement plating method. In the electrolytic treatment method, the pre-plated steel is obtained by immersing the base steel in a sulfuric acid bath or a chloride bath containing metal ions of various pre-plating components and performing electrolytic treatment. In the displacement plating method, the base steel is obtained by immersing it in an aqueous solution containing metal ions of various pre-plating components and pH adjusted with sulfuric acid to precipitate the metal by displacement.

[0085] As a representative example of pre-plated steel, pre-Ni-plated steel can be cited.

[0086] (Plating layer)

[0087] The plating layer includes a Zn-Al-Mg alloy layer. In addition to the Zn-Al-Mg alloy layer, the plating layer may include an Al-Fe alloy layer. The Al-Fe alloy layer is disposed between the base steel and the Zn-Al-Mg alloy layer.

[0088] That is, the plating layer may be a single-layer structure of a Zn-Al-Mg alloy layer, or a multilayer structure including a Zn-Al-Mg alloy layer and an Al-Fe alloy layer. In the case of a multilayer structure, it is preferable that the Zn-Al-Mg alloy layer be the layer constituting the surface of the plating layer.

[0089] However, there are cases where an oxide film of the plating layer constituent elements is formed on the surface of the plating layer at a thickness of about 50 nm, but it is considered to be thin compared to the total thickness of the plating layer (about 8 to 60 μm) and does not constitute the main body of the plating layer.

[0090] The deposition amount of the plating layer is 40 to 300 g / m² per side. 2 It is desirable.

[0091] The adhesion amount of the plating layer is 40 g / m² 2 By doing so, corrosion resistance can be more reliably ensured. In addition, the plating layer adhesion amount is 300 g / m² 2 If reduced to this level, appearance defects such as sagging of the plating layer can be suppressed.

[0092] Next, the chemical composition of the plating layer is explained.

[0093] The chemical composition of the plating layer is, in mass%,

[0094] Zn: Exceeding 65.00%,

[0095] Al: More than 5.00% and less than 25.00%,

[0096] Mg: greater than 3.00% and less than 12.50%,

[0097] Sn: 0% to 3.00%,

[0098] Bi: 0% to less than 5.00%,

[0099] In: 0% to less than 2.00%,

[0100] Ca: 0% to 3.00%,

[0101] Y: 0% to 0.50%,

[0102] La: 0% to less than 0.50%,

[0103] Ce: 0% to less than 0.50%,

[0104] Si: 0% to less than 2.50%,

[0105] Cr: 0% to less than 0.25%,

[0106] Ti: 0% to less than 0.25%,

[0107] Zr: 0% to less than 0.25%,

[0108] Mo: 0% to less than 0.25%,

[0109] W: 0% to less than 0.25%,

[0110] Ag: 0% to less than 0.25%,

[0111] P: 0% to less than 0.25%,

[0112] Ni: 0% to less than 0.25%,

[0113] Co: 0% to less than 0.25%,

[0114] V: 0% to less than 0.25%,

[0115] Nb: 0% to less than 0.25%,

[0116] Cu: 0% to less than 0.25%,

[0117] Mn: 0% to less than 0.25%,

[0118] Li: 0% to less than 0.25%,

[0119] Na: 0% to less than 0.25%,

[0120] K: 0% to less than 0.25%,

[0121] Fe: 0% to 5.00%,

[0122] Sr: 0% to less than 0.50%,

[0123] Sb: 0% to less than 0.50%,

[0124] Pb: 0% to less than 0.50%,

[0125] B: 0% to less than 0.50%, and

[0126] It is made of a chemical composition consisting of impurities.

[0127] In the chemical composition of the plating layer, Sn, Bi, In, Ca, Y, La, Ce, Si, Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, K, Fe, Sr, Sb, Pb, and B are optional components. That is, these elements do not need to be included in the plating layer. If these optional components are included, the content of each optional element is preferably within the range described below.

[0128] Here, the chemical composition of this plating layer is the average chemical composition of the entire plating layer (the average chemical composition of the Zn-Al-Mg alloy layer when the plating layer is a single-layer structure of the Zn-Al-Mg alloy layer, and the average chemical composition of the sum of the Al-Fe alloy layer and the Zn-Al-Mg alloy layer when the plating layer is a stacked structure of the Al-Fe alloy layer and the Zn-Al-Mg alloy layer).

[0129] Below, each element of the plating layer is described.

[0130] Zn: Exceeding 65.00%

[0131] Zn is an element necessary to achieve corrosion resistance. Since the plating layer consists of low-density elements such as Al and Mg when considering the atomic composition ratio, it is necessary to make Zn the dominant element in terms of atomic composition ratio.

[0132] Therefore, the Zn concentration is to be greater than 65.00%. The Zn concentration is preferably 70.00% or higher. In addition, the upper limit of the Zn concentration is the concentration of the remainder excluding elements other than Zn and impurities.

[0133] Al: Greater than 5.00% and less than 25.00%

[0134] Al is an essential element for ensuring corrosion resistance by forming Al crystals. Also, Al is an essential element for ensuring processability by increasing the adhesion of the plating layer. Therefore, the lower limit of the Al concentration is set to be greater than 5.00% (preferably 10.00% or more).

[0135] Meanwhile, if the Al concentration increases too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the Al concentration is set to less than 25.00% (preferably 23.00% or less).

[0136] Mg: Greater than 3.00% and less than 12.50%

[0137] Mg is an essential element for ensuring corrosion resistance. Therefore, the lower limit of the Mg concentration is set to be greater than 3.0% (preferably greater than 4.00%).

[0138] Meanwhile, if the Mg concentration increases too much, processability tends to deteriorate. Therefore, the upper limit of the Mg concentration is set to less than 12.50% (preferably 10.00% or less).

[0139] Sn: 0 to 3.00%

[0140] Sn is an element that contributes to corrosion resistance and resistance to discoloration. Therefore, the lower limit of Sn concentration is preferably greater than 0.00% (preferably 0.05% or more, more preferably 0.10% or more).

[0141] Meanwhile, if the Sn concentration increases too much, the corrosion resistance and early discoloration resistance tend to deteriorate. Therefore, the upper limit of the Sn concentration is set to 3.00% or less.

[0142] Bi: 0% to less than 5.00%

[0143] Bi is an element that contributes to corrosion resistance. Therefore, the lower limit of the Bi concentration is preferably greater than 0.00% (preferably 0.10% or more, more preferably 3.00% or more).

[0144] Meanwhile, if the Bi concentration increases too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the Bi concentration is set to less than 5.00% (preferably 4.80% or less).

[0145] In: 0% to less than 2.00%

[0146] In is an element that contributes to corrosion resistance. Therefore, the lower limit of the In concentration is preferably greater than 0.00% (preferably 0.10% or more, more preferably 1.00% or more).

[0147] Meanwhile, if the In concentration increases too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the In concentration is set to less than 2.00% (preferably 1.80% or less).

[0148] Ca: 0% to 3.00%

[0149] Ca is an element that can adjust the optimal amount of Mg leaching to impart corrosion resistance. Therefore, the lower limit of the Ca concentration is preferably greater than 0.00% (preferably 0.05% or more).

[0150] Meanwhile, if the Ca concentration increases too much, corrosion resistance and processability tend to deteriorate. Therefore, the upper limit of the Ca concentration is set to 3.00% or less (preferably 1.00% or less).

[0151] Y: 0% to 0.50%

[0152] Y is an element that contributes to corrosion resistance. Therefore, the lower limit of the Y concentration is preferably greater than 0.00% (preferably 0.10% or more).

[0153] Meanwhile, if the Y concentration increases too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the Y concentration is set to 0.50% or less (preferably 0.30% or less).

[0154] La and Ce: 0% to less than 0.50%

[0155] La and Ce are elements that contribute to corrosion resistance. Therefore, it is desirable that the lower limit values ​​of La concentration and Ce concentration each be greater than 0.00% (preferably 0.10% or more).

[0156] Meanwhile, if the La concentration and Ce concentration increase too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit values ​​for the La concentration and Ce concentration are each set to less than 0.50% (preferably 0.40% or less).

[0157] Si: 0% to less than 2.50%

[0158] Si is an element that contributes to improved corrosion resistance by inhibiting the growth of the Al-Fe alloy layer. Therefore, it is desirable for the Si concentration to be greater than 0.00% (preferably 0.05% or more, more preferably 0.10% or more). In particular, when Sn is not included (i.e., when the Sn concentration is 0%), it is desirable for the Si concentration to be 0.10% or more (preferably 0.20% or more) from the perspective of ensuring corrosion resistance.

[0159] Meanwhile, if the Si concentration increases too much, corrosion resistance and processability tend to deteriorate. Therefore, the upper limit of the Si concentration is set to less than 2.50%. In particular, from the perspective of corrosion resistance, the Si concentration is preferably 2.40% or less, more preferably 1.80% or less, and even more preferably 1.20% or less.

[0160] Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K: 0% to less than 0.25%

[0161] Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K are elements that contribute to corrosion resistance. Therefore, the lower limit of the concentrations of Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K is preferably greater than 0.00% (preferably 0.05% or more, more preferably 0.10% or more).

[0162] Meanwhile, if the concentrations of Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K increase too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the concentrations of Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K is set to less than 0.25% each. The upper limit of the concentrations of Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K is preferably 0.22% or less.

[0163] Fe: 0% to 5.00%

[0164] When a plating layer is formed by the molten plating method, a constant Fe concentration is contained in the Zn-Al-Mg alloy layer and the Al-Fe alloy layer.

[0165] It has been confirmed that even if Fe is included in a plating layer (especially a Zn-Al-Mg alloy layer) up to a concentration of 5.00%, there is no adverse effect on performance. Since most of the Fe is contained in the Al-Fe alloy layer, the Fe concentration generally increases as the thickness of this layer increases.

[0166] Sr, Sb, Pb, and B: 0% to less than 0.50%

[0167] Sr, Sb, Pb, and B are elements that contribute to corrosion resistance. Therefore, the lower limit of the concentrations of Sr, Sb, Pb, and B is preferably greater than 0.00% (preferably 0.05% or more, more preferably 0.10% or more), respectively.

[0168] Meanwhile, if the concentrations of Sr, Sb, Pb, and B increase too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the concentrations of Sr, Sb, Pb, and B is set to less than 0.50% each.

[0169] impurities

[0170] Impurities refer to components contained in raw materials or introduced during the manufacturing process, which are not intentionally included. For example, in a plating layer, trace amounts of components other than Fe may be incorporated as impurities due to mutual atomic diffusion between the base steel and the plating bath.

[0171] The chemical composition of the plating layer is measured by the following method.

[0172] First, an acid solution is obtained by stripping and dissolving the plating layer using an acid containing an inhibitor that inhibits corrosion of the substrate steel. Next, the chemical composition of the plating layer can be obtained by measuring the obtained acid solution using ICP analysis (the chemical composition of the Zn-Al-Mg alloy layer if the plating layer is a single-layer structure of a Zn-Al-Mg alloy layer, or the chemical composition of the sum of the Al-Fe alloy layer and the Zn-Al-Mg alloy layer if the plating layer is a stacked structure of an Al-Fe alloy layer and a Zn-Al-Mg alloy layer). There are no particular restrictions on the type of acid, as long as it is an acid capable of dissolving the plating layer. Furthermore, the chemical composition is measured as an average chemical composition. Additionally, the Zn concentration in ICP analysis is calculated using the formula: Zn concentration = 100% - concentration of other elements (%).

[0173] Here, if pre-plated steel is used as the base steel, the components of the pre-plating are also detected.

[0174] For example, when using pre-Ni plated steel, ICP analysis detects not only Ni in the plating layer but also Ni in the pre-Ni plating. Specifically, for example, when the Ni deposition amount is 1 g / m² 2 Up to 3g / m 2 When a pre-plated steel (thickness of about 0.1 to 0.3 μm) is used as a base steel, even if the Ni concentration contained in the plating layer is 0%, the Ni concentration is detected as 0.1 to 15% when measured by ICP analysis.

[0175] Here, the method for determining whether the base steel is a pre-Ni plated steel is as follows.

[0176] A sample is taken from the target steel material, wherein the cross-section cut along the thickness direction of the plating layer serves as the measurement surface.

[0177] With respect to the measurement surface of the sample, the area near the interface between the plating layer and the substrate steel in the steel is line-analyzed using an electron probe microanalyzer (FE-EPMA) to measure the Ni concentration. The measurement conditions are an acceleration voltage of 15 kV, a beam diameter of approximately 100 nm, an irradiation time per point of 1000 ms, and a measurement pitch of 60 nm. In addition, the measurement distance is sufficient to confirm whether the Ni concentration is enriched at the interface between the plating layer and the substrate steel in the steel.

[0178] And if the Ni concentration is concentrated at the interface between the plating layer and the base steel, the base steel is determined to be pre-Ni plated steel.

[0179] In addition, when a pre-Ni plated steel is used as the base steel, the Ni concentration of the plating layer is defined as the value measured as follows.

[0180] First, using a high-frequency glow discharge surface analysis device (GDS: manufactured by Horiba Seisakusho, model number: GD-Profiler2), the luminescence intensity of Ni is measured for three or more types of standard samples with different Ni concentrations (BAS Zn alloy standard samples IMN ZH1, ZH2, ZH4). A calibration curve is prepared from the relationship between the obtained Ni luminescence intensity and the Ni concentration in the standard formula.

[0181] Next, the luminescence intensity of Ni at the half-thickness of the plating layer of the plated steel material to be measured is measured using a high-frequency glow discharge surface analysis device (GDS: manufactured by Horiba Seisakusho, model number: GD-Profiler2). From the obtained luminescence intensity of Ni and the calibration curve prepared, the Ni concentration at the half-thickness of the plating layer is determined. The obtained Ni concentration at the half-thickness of the plating layer is defined as the Ni concentration of the plating layer.

[0182] And when a pre-Ni plated steel is used as the base steel, the Zn concentration of the plating layer is defined as the Zn concentration calculated from the following formula.

[0183] Formula: Zn concentration = 100 - (Concentration of elements other than Zn and Ni obtained by ICP analysis + Ni concentration obtained by GDS)

[0184] In addition, the measurement conditions of the high-frequency glow discharge luminescent surface analysis device are as follows.

[0185] ·HV: 630V

[0186] · Anode diameter: φ4mm

[0187] · Gas: Ar

[0188] · Gas pressure: 600Pa

[0189] · Output: 35W

[0190] Next, the Al-Fe alloy layer is explained.

[0191] The Al-Fe alloy layer is formed on the surface of the base steel (specifically, between the base steel and the Zn-Al-Mg alloy layer) and is a layer in which the Al5Fe phase is the main phase as the microstructure. The Al-Fe alloy layer is formed by mutual atomic diffusion between the base steel and the plating bath. Since the steel of the present disclosure forms a plating layer by a molten plating method, the Al-Fe alloy layer is easily formed in the plating layer containing Al elements. Since the plating bath contains Al at a concentration above a certain level, the Al5Fe phase is formed most abundantly. However, atomic diffusion takes time, and there are also parts where the Fe concentration is high in the portion close to the base steel. Therefore, the Al-Fe alloy layer may partially contain small amounts of AlFe, Al3Fe, Al5Fe2 phases, etc. Additionally, since the plating bath contains Zn at a certain concentration, the Al-Fe alloy layer also contains small amounts of Zn.

[0192] There is no significant difference in the corrosion resistance of the Al5Fe, Al3Fe, AlFe, and Al5Fe2 phases. The corrosion resistance referred to here is the corrosion resistance in parts unaffected by welding.

[0193] Here, when the plating layer contains Si, Si is particularly easily introduced into the Al-Fe alloy layer, and may form an Al-Fe-Si intermetallic compound phase. Among the identified intermetallic compound phases, there is the AlFeSi phase, and as isomers, α, β, q1, q2-AlFeSi phases exist. Therefore, these AlFeSi phases may be detected in the Al-Fe alloy layer. An Al-Fe alloy layer containing these AlFeSi phases is also referred to as an Al-Fe-Si alloy layer.

[0194] In addition, since the thickness of the Al-Fe-Si alloy layer is smaller than that of the Zn-Al-Mg alloy layer, its influence on the corrosion resistance of the entire plating layer is small.

[0195] In addition, when various types of pre-plated steel are used as the base steel, the structure of the Al-Fe alloy layer may change depending on the amount of pre-plating applied. Specifically, this includes cases where a pure metal layer used for pre-plating remains around the Al-Fe alloy layer, cases where an intermetallic compound phase (e.g., Al3Ni phase) formed by the combination of the constituent components of the Zn-Al-Mg alloy layer and the pre-plating components forms an alloy layer, cases where an Al-Fe alloy layer is formed in which some Al and Fe atoms are substituted, or cases where an Al-Fe-Si alloy layer is formed in which some Al, Fe, and Si atoms are substituted.

[0196] That is, the Al-Fe alloy layer is a layer that includes, in addition to the alloy layer mainly composed of the Al5Fe phase, the various forms of alloy layers mentioned above.

[0197] In addition, among various pre-plated steel materials, when a plating layer is formed on pre-Ni plated steel, an Al-Ni-Fe alloy layer is formed as an Al-Fe alloy layer.

[0198] The thickness of the Al-Fe alloy layer is, for example, 0㎛ or more and 7㎛ or less.

[0199] The thickness of the Al-Fe alloy layer is preferably 0.05㎛ or more and 5㎛ or less from the perspective of increasing the adhesion of the plating layer (specifically, the Zn-Al-Mg alloy layer) and ensuring corrosion resistance and processability.

[0200] Typically, since the Zn-Al-Mg alloy layer is thicker than the Al-Fe alloy layer, the contribution of the Al-Fe alloy layer to the corrosion resistance of the plated steel is smaller compared to that of the Zn-Al-Mg alloy layer. However, as estimated from the results of compositional analysis, the Al-Fe alloy layer contains Al and Zn, which are corrosion-resistant elements, at concentrations above a certain level. Therefore, the Al-Fe alloy layer possesses a certain degree of corrosion resistance to the base steel.

[0201] In addition, when a plating layer of the chemical composition specified in the present disclosure is formed by a molten plating method, an Al-Fe alloy layer of 100 nm or more is often formed between the base steel and the Zn-Al-Mg alloy layer.

[0202] From the perspective of corrosion resistance, a thicker Al-Fe alloy layer is desirable. Therefore, the thickness of the Al-Fe alloy layer is preferably 0.05 μm or more. However, since a thick Al-Fe alloy layer causes significant deterioration in machinability, the thickness of the Al-Fe alloy layer is preferably 7 μm or less. If the thickness of the Al-Fe alloy layer is 7 μm or less, the amount of cracks and powdering originating from the Al-Fe alloy layer is reduced, thereby improving machinability. The thickness of the Al-Fe alloy layer is more preferably 5 μm or less, and even more preferably 2 μm or less.

[0203] The thickness of the Al-Fe alloy layer is measured as follows.

[0204] After embedding the sample in resin and polishing it, the thickness of the identified Al-Fe alloy layer is measured at any five locations in the SEM reflection electron image of the cross-section of the plating layer (cross-section along the thickness direction of the plating layer) (provided that the magnification is 10,000x and the field of view is 50㎛ vertically × 200㎛ horizontally, so that the Al-Fe alloy layer is visible). Then, the arithmetic mean of the five locations is taken as the thickness of the Al-Fe alloy layer.

[0205] In addition, regarding the thickness of the plating layer, the thickness is measured at any five locations in the reflection electron image of the cross-sectional SEM (provided that the magnification is 500x and the field of view is 198㎛ in height × 244㎛ in width, so that the entire plating layer is visible). Then, the arithmetic mean of the five locations is taken as the thickness of the plating layer.

[0206] (Characteristics of galvanized steel)

[0207] -Average value of cumulative periphery length of Zn / Al / MgZn23- process-

[0208] In the back-field electron image of the Zn-Al-Mg alloy layer obtained by observing the surface of the plating layer at a magnification of 100x using a scanning electron microscope after polishing it to half the layer thickness, a Zn / Al / MgZn23-membered process exists, and the average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process is 100 to 300 mm / mm 2 am.

[0209] The average value of the cumulative perimeter length of the Zn / Al / MgZn23 process is 100mm / mm 2 If the value is below this level, the Zn / Al / MgZn23-membered eutectic, which causes localized corrosion, coarsens, leading to a deterioration in corrosion resistance. In particular, when used in environments where water tends to accumulate, the Zn / Al / MgZn23-membered eutectic within the plating layer corrodes locally, causing corrosion to reach the steel prematurely. Furthermore, when the plated steel is processed, the Zn / Al / MgZn23-membered eutectic fails to function as a buffer; consequently, the intermetallic compound phases crack, making the plating layer prone to peeling and reducing workability.

[0210] The average value of the cumulative perimeter length of the Zn / Al / MgZn23 process is 300 mm / mm 2 If it exceeds , the Zn / Al / MgZn23-membered process becomes too fine, so when the plated steel is processed, the Zn / Al / MgZn23-membered process does not function as a buffer, the intermetallic compound phase cracks, and the plating layer becomes prone to peeling, resulting in reduced processability.

[0211] Therefore, the average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process is 100 to 300 mm / mm 2 The average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process is 105 to 290 mm / mm 2 It is preferable, and 110 to 280 mm / mm 2 It is more desirable.

[0212] In the reflection electron image of the Zn-Al-Mg alloy layer, the area fraction of the Zn / Al / MgZn23-membered process is not particularly limited, but from the viewpoint of processability and corrosion resistance, 10 to 50% is preferred, and 13 to 45% is more preferred.

[0213] Examples of residual structures other than the Zn / Al / MgZn23 process include Al crystals and MgZn2 phases.

[0214] Here, the measurement method for the average value of the cumulative periphery length of the Zn / Al / MgZn23-phase process and the area fraction of the Zn / Al / MgZn23-phase process is described.

[0215] The average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process and the area fraction of the Zn / Al / MgZn23-membered process are measured using the reflected electron image of the Zn-Al-Mg alloy layer obtained by observing it at a magnification of 100x using a scanning electron microscope after polishing the surface of the plating layer to half the layer thickness. Specifically, as follows.

[0216] First, a sample is taken from the plated steel to be measured. However, the sample is taken from a location other than near the punched end surface of the plated steel (2 mm from the end surface) and where there are no defects in the plating layer.

[0217] Next, the surface of the plating layer of the sample (substantially a Zn-Al-Mg alloy layer) is polished in the thickness direction of the plating layer (hereinafter also referred to as the "Z-axis direction").

[0218] Specifically, the surface of the plating layer is dry-polished with a #1200 grit abrasive sheet, and then finished polished using a finishing solution containing alumina with an average particle size of 3 μm, a finishing solution containing alumina with an average particle size of 1 μm, and a finishing solution containing colloidal silica, respectively, in this order.

[0219] In addition, the Zn strength of the surface of the plating layer is measured by XRF (X-ray Fluorescence) before and after polishing, and the point at which the Zn strength after polishing becomes half of the Zn strength before polishing is defined as half of the plating layer thickness. Since the Zn-Al-Mg alloy layer occupies more than half of the plating layer thickness, the polished surface of the plating layer polished to half of the layer thickness becomes the polished surface of the Zn-Al-Mg alloy layer. Therefore, by analyzing the said polished surface, the metal structure contained in the Zn-Al-Mg alloy layer can be identified.

[0220] Next, the polished surface is observed at a magnification of 100x using a scanning electron microscope (SEM) to obtain a back-field electron image (hereinafter also referred to as the “back-field electron image of the SEM”). The SEM observation conditions are set as follows: acceleration voltage: 15 kV, irradiation current: 10 nA, and field of view size: 1000 µm × 800 µm.

[0221] The Zn / Al / MgZn23-phase process is identified in the SEM reflection electron image (grayscale image stored in 8-bit, 256-color display) using the binary processing function based on two thresholds of Shoji Mitani's WinROOF 2015 (image analysis software). In addition, in the grayscale image stored in 8-bit, black appears when the luminosity is 0, and white appears when the maximum value is 255. Typically, phases with a higher content of Al and Mg, which have smaller atomic numbers, tend to appear blacker, while phases with a higher content of Zn tend to appear whiter. Among the microstructures of the plating layer, the microstructure that appears whitest is the Zn / Al / MgZn23-phase process (see Figure 1 (A)).

[0222] In the case of SEM reflection electron images, it was determined from identification results by FE-SEM or TEM that Zn / Al / MgZn23-phase processes can be identified with high precision when the luminance thresholds are set to 160 and 215. Therefore, Zn / Al / MgZn23-phase processes are identified by processing the images so that the color changes within the luminance range of 160 to 215 (see (B) in Fig. 1).

[0223] Next, using the automatic shape feature measurement function of Shoji Mitani’s WinROOF 2015 (image analysis software), the perimeter lengths of the Zn / Al / MgZn23-cycle process identified by the image processing are accumulated to obtain the accumulated perimeter length of the Zn / Al / MgZn23-cycle process. Then, the accumulated perimeter length of the Zn / Al / MgZn23-cycle process is divided by the field of view area to obtain a unit area (mm²). 2 Calculate the cumulative perimeter length of the Zn / Al / MgZn23 process per )

[0224] Perform this operation in 3 fields of view, and per unit area (mm² 2 The arithmetic mean of the cumulative perimeter length of the Zn / Al / MgZn23-won process per ) is set as the “average value of the cumulative perimeter length of the Zn / Al / MgZn23-won process”.

[0225] In addition, the area fraction of the Zn / Al / MgZn23-phase process can also be obtained using the automatic shape feature measurement function of Shoji Mitani's WinROOF 2015 (image analysis software). Specifically, the area fraction of the Zn / Al / MgZn23-phase process (area fraction relative to the viewing area) identified by binarization in the reflected electron image of the Zn-Al-Mg alloy layer is calculated using this function. Then, this operation is performed in three viewing areas, and the arithmetic mean is taken as the area fraction of the "Zn / Al / MgZn23-phase process."

[0226] (Method for manufacturing plated steel)

[0227] Hereinafter, an example of a method for manufacturing plated steel according to the present disclosure will be described.

[0228] The plated steel of the present disclosure is obtained by forming a plating layer having the above-mentioned predetermined chemical composition and metallic structure on the surface (i.e., one side or both sides) of a base steel (base steel plate, etc.) by a molten plating method.

[0229] Specifically, as an example, molten plating treatment is performed under the following conditions.

[0230] For example, a steel substrate having a surface roughness Ra of 0.3 to 2.0 μm on the plated surface is immersed in a plating bath, and after being removed from the plating bath, it is cooled in a temperature range of 450 to 395°C at an average cooling rate of 5 to 20°C / s.

[0231] Next, the temperature range of 395 to 340°C is cooled at an average cooling rate of 3°C / s or less.

[0232] Next, the temperature range of 340 to 280℃ is cooled at an average cooling rate of 10 to 20℃ / s.

[0233] Here, the plating is carried out using a continuous molten metal plating method, such as the Sendzimir method, for example.

[0234] By making the surface roughness Ra of the plated surface of the substrate steel 0.3 μm or more, solidification nuclei of the plating layer structure are easily formed, so that Al primary crystals are densely precipitated. As a result, the Zn / Al / MgZn23-membered process is finely dispersed, and the average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process can be controlled to the above range.

[0235] However, if the surface roughness Ra of the plated surface of the substrate steel exceeds 2.0㎛, the wettability of the plating deteriorates, making it easy for the plating to be incomplete.

[0236] The surface roughness Ra of the plated surface of the base steel is measured as follows in accordance with JIS B 0633:2001. For the plated surface of the base steel prior to plating, the average surface roughness is measured three times at a length of 10 mm in each of two arbitrary directions forming a 90° angle using a contact-type surface roughness meter. The arithmetic mean of the obtained average surface roughness measurements (a total of 6 measurements: 2 directions × 3 times) is calculated. This arithmetic mean value is set as the surface roughness Ra of the plated surface of the base steel.

[0237] When measuring the interfacial roughness Ra between the base steel and the plating layer, first, the plating layer is removed from the plated steel by dissolving it with hydrochloric acid to which an inhibitor has been added. Then, the surface of the base steel on the side from which the plating layer was removed is measured and the average value is calculated in the same manner as above. This is defined as the interfacial roughness Ra between the base steel and the plating layer.

[0238] In the present disclosure, the interface roughness Ra between the base steel and the plating layer in the plated steel (i.e., after plating) and the surface roughness Ra of the plated surface of the base steel before plating generally coincide. That is, by using a base steel having a surface roughness Ra of the plated surface of 0.3 to 2.0 μm, the interface roughness Ra between the base steel and the plating layer in the plated steel obtained can be 0.3 to 2.0 μm.

[0239] Here, the plating layer solidifies in the order of Al primary phase, Al / MgZn2 phase, MgZn2 peritectic precipitating around the Al primary phase, and Zn / Al / MgZn23 eutectic.

[0240] Therefore, by cooling the temperature range of 450 to 395°C at an average cooling rate of 5°C / s or higher, Al primary crystals and Al / MgZn2 phases are finely dispersed. Then, by cooling the temperature range of 395 to 340°C at an average cooling rate of 3°C / s or lower, MgZn2 peritectic crystals are reliably precipitated around the Al primary crystals. By doing so, the Zn / Al / MgZn23-phase can be refined.

[0241] However, if the average cooling rate in the temperature range of 450 to 395°C exceeds 20°C / s, the Al primary crystals and Al / MgZn2 phases precipitate too finely, and the Zn / Al / MgZn23-phase process is also excessively refined. In that case, the average value of the cumulative periphery length of the Zn / Al / MgZn23-phase process exceeds the above range.

[0242] Next, by cooling the temperature range of 340 to 280°C at an average cooling rate of 10 to 20°C / s, the Zn / Al / MgZn23-membered process is refined. By doing so, the average value of the cumulative peripheral length of the Zn / Al / MgZn23-membered process is controlled to the above range.

[0243] Hereinafter, post-treatments applicable to the plated steel of the present disclosure will be described.

[0244] The plated steel of the present disclosure may have a film formed on the plating layer. The film may be formed in one layer or two or more layers. Examples of the types of films immediately above the plating layer include chromate films, phosphate films, and chromate-free films. The chromate treatment, phosphate treatment, and chromate-free treatment for forming these films may be performed by known methods.

[0245] Chromate treatments include electrolytic chromate treatment, which forms a chromate film by electrolysis; reactive chromate treatment, which forms a film by reacting with the material and then washes off the excess treatment solution; and coating chromate treatment, which forms a film by applying a treatment solution to the workpiece and drying it without rinsing. Any of these treatments may be adopted.

[0246] Examples of electrolytic chromate treatment include chromic acid, silica sol, resin (acrylic resin, vinyl ester resin, vinyl acetate acrylic emulsion, carboxylated styrene butadiene latex, diisopropanolamine modified epoxy resin, etc.), and hard silica.

[0247] Examples of phosphate treatments include zinc phosphate treatment, zinc calcium phosphate treatment, and manganese phosphate treatment.

[0248] Chromate-free treatment is particularly suitable because it places no burden on the environment. Chromate-free treatments include electrolytic chromate-free treatment, which forms a chromate-free film by electrolysis; reactive chromate-free treatment, which forms a film by reacting with the material and then washes away excess treatment liquid; and coating chromate-free treatment, which forms a film by applying a treatment liquid to the workpiece and drying it without rinsing. Any of these treatments may be adopted.

[0249] In addition, one or more layers of organic resin film may be provided on the film immediately above the plating layer. The organic resin is not limited to a specific type and may include, for example, polyester resin, polyurethane resin, epoxy resin, acrylic resin, polyolefin resin, or modified products of these resins. Here, a modified product refers to a resin in which a reactive functional group included in the structure of these resins is reacted with another compound (monomer or crosslinking agent, etc.) that includes a functional group capable of reacting with said functional group in its structure.

[0250] As for such organic resins, one or more types of organic resins (that are not modified) may be mixed and used, or one or more types of organic resins obtained by modifying at least one other organic resin in the presence of at least one organic resin may be mixed and used. In addition, any coloring pigment or anti-corrosion pigment may be included in the organic resin film. Water-based resins obtained by dissolving or dispersing in water may also be used.

[0251] (Example)

[0252] A plating bath was prepared in the atmosphere using a predetermined amount of pure metal ingot so that a plating layer with the chemical composition shown in Tables 1 and 2 could be obtained. A molten plating simulator was used to produce the plated steel sheet.

[0253] As the substrate steel, a general-purpose hot-rolled steel sheet with a thickness of 2.3 mm (C concentration < 0.1%) was used, brush-polished, and degreasing and pickling were performed immediately before the plating process. The surface roughness Ra (indicated as "surface roughness Ra" in the table) of the plated surface of the substrate steel was as shown in Tables 1 and 2.

[0254] In addition, in some examples, pre-Ni plated steel, which had undergone pre-Ni plating, was used as the base steel. The Ni coating amount was 1 g / m² 2 Up to 3g / m 2 In addition, examples where pre-Ni plated steel was used as the base steel were indicated as "pre-Ni" in the "base steel" column of the table.

[0255] A contact-type K thermocouple was installed on the back side of the plated surface of the base steel to monitor the temperature of the steel during the plated steel sheet manufacturing process.

[0256] In the preparation of each sample, an equivalent reduction treatment method was performed on the steel substrate before immersion in the plating bath. Specifically, the steel substrate was heated from room temperature to 800°C by electric heating in an N2-H2 (5%) environment (dew point -40°C or lower, oxygen concentration less than 25 ppm), maintained for 60 seconds, then cooled to the plating bath temperature + 10°C by N2 gas injection, and immediately immersed in the plating bath.

[0257] In addition, for each plated steel sheet, the plating bath temperature was based on 500°C, and in some cases, the temperature was increased to a higher level. The immersion time in the plating bath was set to the time (2 seconds) in the table. The N2 gas wiping pressure was adjusted so that the plating thickness was 30 μm (±1 μm).

[0258] Then, after pulling the substrate steel out of the plating bath, a plating layer was obtained by a cooling process in which the average cooling rate of the 1st to 3rd stages shown in Tables 1 to 2 was set to the conditions shown in Tables 1 to 2.

[0259] · 1st stage average cooling rate: Average cooling rate for the temperature range of 450 to 395℃

[0260] · 2nd stage average cooling rate: Average cooling rate in the temperature range of 395 to 340℃

[0261] · 3rd stage average cooling rate: Average cooling rate for the temperature range of 340 to 280°C

[0262] In addition, during the cooling process, the steel was cooled by injecting N2 gas onto the steel after plating. At this time, cooling was performed while adjusting the amount of N2 gas injected to achieve a predetermined cooling rate within the aforementioned temperature range.

[0263] -Various Measurements-

[0264] A sample was cut from the obtained plated steel sheet. Then, according to the method previously described, the following items were measured.

[0265] · Average value of the cumulative perimeter of the Zn / Al / MgZn 23-stage process (indicated as "perimeter of the 3-stage process" in the table)

[0266] · Area fraction of the Zn / Al / MgZn 23-stage process (indicated as "Area fraction of the 3-stage process" in the table)

[0267] · Thickness of the Al-Fe alloy layer (however, in examples where a pre-Ni plated steel sheet is used as the base steel, the thickness of the Al-Ni-Fe alloy layer is indicated)

[0268] -Machinability-

[0269] A sample was cut from the obtained plated steel sheet. Then, after bending the sample to 1T, the tape was peeled off the processed part, and the area ratio of the plating layer attached to the tape was evaluated. An area ratio of 5% or less of the attached plating layer was evaluated as “A”, and an area ratio of more than 5% was evaluated as “NG”.

[0270] -Corrosion resistance-

[0271] A sample was cut from the obtained galvanized steel sheet. The sample was then placed flat, and a combined cycle corrosion test (CCT) in accordance with the accelerated corrosion test (JASO M609-91) was performed for 21 cycles. After the corrosion test, the corrosion loss was 35 g / m². 2 If it is less than or equal to 35g / m², it is evaluated as "A". 2 Excess was evaluated as "NG".

[0272] Examples are listed in Tables 1 and 2.

[0273] [Table 1-1]

[0274]

[0275] [Table 1-2]

[0276]

[0277] [Table 1-3]

[0278]

[0279] [Table 1-4]

[0280]

[0281] [Table 2-1]

[0282]

[0283] [Table 2-2]

[0284]

[0285] [Table 2-3]

[0286]

[0287] [Table 2-4]

[0288]

[0289] From the above results, it can be seen that the embodiment corresponding to the plated steel of the present disclosure exhibits excellent corrosion resistance even when used in an environment where water tends to accumulate, along with processability, compared to the comparative example.

[0290] In Test No. 95, the perimeter length and area fraction of the ternary process were not measured because there was a large variation in appearance due to the presence of multiple unplated areas.

[0291] Although suitable embodiments and examples of the present disclosure have been described in detail above with reference to the accompanying drawings, the present disclosure is not limited to such examples. It is clear to those skilled in the art to which the present disclosure pertains that various modifications or variations can be made within the scope of the technical concept described in the claims, and these are also naturally understood to fall within the technical scope of the present disclosure.

[0292] Additionally, the disclosure of Japanese Patent Application No. 2022-044295 is incorporated herein by reference in its entirety.

[0293] All documents, patent applications, and technical specifications described in this specification are incorporated by reference in this specification to the same extent that individual documents, patent applications, and technical specifications are incorporated by reference as they are specifically and individually described.

Claims

Claim 1 A plated steel having a base steel and a plating layer comprising a Zn-Al-Mg alloy layer disposed on the surface of the base steel, wherein the plating layer comprises, in mass%, Zn: greater than 65.00%, Al: greater than 5.00% to less than 25.00%, Mg: greater than 3.00% to less than 12.50%, Sn: 0% to 3.00%, Bi: 0% to less than 5.00%, In: 0% to less than 2.00%, Ca: 0% to 3.00%, Y: 0% to 0.50%, La: 0% to less than 0.50%, Ce: 0% to less than 0.50%, Si: 0% to less than 2.50%, Cr: 0% to less than 0.25%, Ti: 0% to less than 0.25%, and Zr: 0% to 0.25%. Less than, Mo: 0% to less than 0.25%, W: 0% to less than 0.25%, Ag: 0% to less than 0.25%, P: 0% to less than 0.25%, Ni: 0% to less than 0.25%, Co: 0% to less than 0.25%, V: 0% to less than 0.25%, Nb: 0% to less than 0.25%, Cu: 0% to less than 0.25%, Mn: 0% to less than 0.25%, Li: 0% to less than 0.25%, Na: 0% to less than 0.25%, K: 0% to less than 0.25%, Fe: 0% to 5.00%, Sr: 0% to less than 0.50%, Sb: 0% to less than 0.50%, Pb: 0% to 0.50% It has a chemical composition consisting of less than, B: 0% to less than 0.50%, and impurities, wherein the upper limit of the Zn concentration is the concentration of the remainder excluding elements other than Zn and impurities, and in the back-field electron image of the Zn-Al-Mg alloy layer obtained by observing at a magnification of 100x using a scanning electron microscope after polishing the surface of the plating layer to 1 / 2 of the layer thickness, a Zn / Al / MgZn23-membered process exists, and the average value of the cumulative periphery length of the Zn / Al / MgZn23-membered process is 100 to 300 mm / mm 2 Phosphorized steel. Claim 2 In claim 1, the plating layer comprises an Al-Fe alloy layer between the base steel and the Zn-Al-Mg alloy layer, forming a plated steel. Claim 3 A plated steel according to claim 1 or 2, wherein the interface roughness Ra between the base steel and the plating layer is 0.3 to 2.0 μm. Claim 4 A method for manufacturing a plated steel material according to claim 1 or 2, wherein a base steel material having a surface roughness Ra of 0.3 to 2.0 μm on the plated surface is immersed in a plating bath, and after being removed from the plating bath, the base steel material is cooled in a temperature range of 450 to 395°C at an average cooling rate of 5 to 20°C / s, the base steel material is cooled in a temperature range of 395 to 340°C at an average cooling rate of 3°C / s or less, and the base steel material is cooled in a temperature range of 340 to 280°C at an average cooling rate of 10 to 20°C / s.

Citation Information

Patent Citations

  • Zinc alloy-plated steel sheet excellent in weldability and corrosion resistance of processed parts and method for producing the same

    JP2018506644A

  • Plated steel material

    WO2021095442A1